Food security - Stifel, David; Hassen, Ibrahim Worku (International Food Policy Research Institute, 2020)
Chapter 10, “Food Security,” describes the evolution of poverty and food security between 2010/2011 and 2015/2016 and examines the seasonality of food insecurity. Household survey data from 2016 show that Ethiopia continues to face high levels of food insecurity: daily energy consumption is low (3,055 kilocalories per adult on average), and diet quality is poor (starchy staples account for 71.6 percent of calories). There has been relatively little change in the composition of diets between 2011 and 2016, although the diets of the poorest half of the population (especially in rural areas) improved slightly with less reliance on starchy staples and greater dietary diversity. The authors find substantial seasonal patterns, however, with marked variations in energy (calorie) consumption, which is highest in postharvest periods. Regression analysis using the 2015/2016 data reveals that that average energy intake is positively associated with total household expenditure and productive farm